2016
DOI: 10.1084/jem.20160397
|View full text |Cite
|
Sign up to set email alerts
|

Elp3 links tRNA modification to IRES-dependent translation of LEF1 to sustain metastasis in breast cancer

Abstract: Delaunay et al. reveal the role of U34 tRNA-modifying enzymes in the regulation of specific mRNA translation to support cell invasion and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 77 publications
(119 reference statements)
0
120
1
1
Order By: Relevance
“…This indicated that MYCBP may be one of the targets of LEF-1. LEF-1 has previously been reported to be expressed excessively and to function as an oncogene in numerous types of cancer (36). Furthermore, the TCF/LEF axis serves a crucial role in the Wnt/β-catenin signaling pathway, and the Wnt signaling pathway has been shown to be involved in a number of cellular functions, including cell proliferation, survival, and differentiation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that MYCBP may be one of the targets of LEF-1. LEF-1 has previously been reported to be expressed excessively and to function as an oncogene in numerous types of cancer (36). Furthermore, the TCF/LEF axis serves a crucial role in the Wnt/β-catenin signaling pathway, and the Wnt signaling pathway has been shown to be involved in a number of cellular functions, including cell proliferation, survival, and differentiation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the enzymes responsible for mcm 5 s 2 modification, ELP3 and CTU1/2, have been found to be up-regulated in breast cancer and to sustain metastasis (Delaunay et al 2016). Similarly, the methyltransferase NSUN2 has been found to be overexpressed in breast cancer and its expression levels have been shown to correlate with cancer development and progression .…”
Section: Wwwrnajournalorg 1759mentioning
confidence: 99%
“…In regard to tRNA modifications, their functions include: stability and flexibility of the tRNA structure (Motorin and Helm 2010), translational fidelity via codon-anticodon interaction (Saint-Léger and Ribas de Pouplana 2015), reading frame maintenance (Waas et al 2007;Delaunay et al 2016;Klassen et al 2016a), tRNA discrimination , nonsense suppression (Benko et al 2000), tRNA stability (Alexandrov et al 2006;Kotelawala et al 2008;Dewe et al 2012), proteome integrity (Nedialkova and Leidel 2015), sensitivity to aminoglycoside antibiotics acting at the decoding site of ribosomes (Kalhor and Clarke 2003), response to stress (Kamenski et al 2007;Chan et al 2012;Gu et al 2014), and recognition of tRNA as either self or nonself by TLR7 receptor (Kaiser et al 2014;Rimbach et al 2015). For general reviews, see Helm (2011), Hopper (2013) and Phizicky and Hopper (2015).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Their alterations result in severe consequences during translation, such as misreading, frame shifts, translation shifted to another distant site, as well as diverse pleiotropic cellular effects, including pathological states (Wei and Tomizawa 2011;Delaunay et al 2016). The three cases are clear examples of the links between tRNA modification and the cellular metabolic state.…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%